Late Recurrence of Osteosarcoma: A Report of Two Cases. (December 2014) - Igarashi, Kentaro; Yamamoto, Norio; Shirai, Toshiharu; Nishida, Hideji; Hayashi, Katsuhiro; Tanzawa, Yoshikazu; Kimura, Hiroaki; Takeuchi, Akihiko; Miwa, Shinji; Inatani, Hiroyuki; Shimozaki, Shingo; Kato, Takashi; et al.
We report 2 cases of late recurrence of osteosarcoma after 6 and 7 years. One patient had pulmonary metastasis, and the other had soft tissue recurrence. Both patients underwent complete resection and chemotherapy. The first patient achieved complete remission and remained disease-free 47 months later and had no limitation in his daily life. The second patient had a re-recurrence and underwent further resection and chemotherapy. He remained disease-free 35 months later and could walk using a T-handled walking cane.